Internal control, related party transactions and corporate value of enterprises directly controlled by Chinese central government - Yan Tong; Mingzhu Wang; Feng Xu (Journal of Chinese Management, 2014)
State-owned enterprises (SOEs) play a crucial role in China's economy. Those directly controlled by the central government (CSOEs) take leading positions almost in all industries in China. In this paper, we analyse the impacts of internal control quality of CSOEs on related party transactions and corporate value of CSOEs after the Chinese government introduced regulatory changes and the split share structure reform. Current literature offers little empirical evidence in this area. The primary information collected from 167 questionnaires responded by 22 CSOEs is analysed using structural equation models. We find that internal controls of a higher quality reduce unfair related party transactions for private benefits at the cost of corporate value and hence increase the corporate value of CSOEs. However, the overall perception of the internal control quality of CSOEs is not satisfactory with a mean of 5.3174 based on a seven-point Likert scale. This indicates that effective implementation of internal control is critical for CSOEs after setting up regulations and systems.
Keywords: 650; Internal control; Related party transactions; Corporate value; CSOEs